Non-sugar sweeteners and children: the current picture and controversies - Campos, Maria João; Silva, Liliana J. G.; Pereira, André M. P. T.; Pena, Angelina (Frontiers in Nutrition, 2025)
The global effort to reduce childhood obesity and type 2 diabetes has increased the use of non-sugar sweeteners (NSS) as alternatives to sugar. However, the long-term health effects of NSS in children remain debated, with inconsistent evidence supporting a precautionary approach. This perspective article critically reviews current knowledge, highlights research gaps, and questions the broader context of NSS usage. There is a general consensus that the use of NSS is inadvisable before age 3 and strongly discouraged for those up to age 5. Beyond this age, uncertainties persist, especially regarding the benefits and risks for children who are overweight, obese, or have diabetes. There is an urgent need for robust, long-term studies on NSS exposure in children. Current regulatory measures such as varied labelling, school restrictions, and taxation reflect the lack of a unified scientific consensus and harmonised policies. To effectively protect children’s health, it is essential to establish a global agreement and develop evidence-based guidelines on the use of NSS.